The Little Street by Johannes Vermeer: Nieuwe Langendijk 22-26? An art historian's view on archeological and historical-architectural research (Bulletin KNOB, 2000)
Remarkably little has been written about the popular yet unassuming painting The Little Street (Rijksmuseum, Amsterdam). This painting shows a group of houses in Delft. The large house at the right hand side is analyzed in great detail and yields precise architectural information. The building just escaped the great Delft fire of 1536 (ill. 10). The facade of this house had a wooden structure. The masonry is well observed as is the pattern of cracks in the walls, which could not have been known to a layman. The gutter leading water across the street towards us indicates that the house stood along a canal, not along a regular street.Crucial information is also yielded by another house, which we can see towards the middle background, having a position which is highly unusual in terms of real estate alignment (ill. 5 and 6). Analysis of the roof structure of nr. 22 showed that once it had a lean-to side room. This combination of elements points towards certain possible locations along certain canals within Delft.In 1982 the engineering student Wim Weve (since 1987 architectural historian for the town of Delft) was the first to propose the identification of Vermeer's Little Street and the site at Nieuwe Langendijk nrs. 22-26. These very buildings were carefully studied by a Delft Polytechnic university team in the spring and early summer of 1982, before, during and after demolition. An extremely detailed three volume report on this excavation was published by Van Haaften in 1987 at the Delft Polytechnic.The present article fully accepts their identification which has not become known let alone accepted in art history circles. Finally a set of arguments, some of them new ones, offers a tapestry of detailed proof for this identification. The English language readers are referred to the discussion in my forthcoming chapter in Wayne Franits (ed.) The Cambridge Companion to Vermeer. Cambridge University Press, 2001. A full bilingual text is on internet, http://www.xs4all.nl/~kalden/